An “I Do” I Choose: How the Fight for Marriage Access Supports a Per Se Finding of Persecution for Asylum Cases Based on Forced Marriage - Nanasi, Natalie (Columbia Journal of Gender and Law, 2014)
In the summer of 2013, the country waited anxiously for the Supreme Court to issue rulings in two landmark gay marriage cases that had the potential to fundamentally alter the institution of marriage in the United States. Advocates and opponents of same-sex unions fiercely debated the issue, but although the two sides’ positions were widely divergent, each emphasized the unique role of marriage in the social, personal, and legal fabric of life. Edie Windsor, the named plaintiff in the lawsuit seeking to strike down § 3 of the Defense of Marriage Act (DOMA), agreed. Ms Windsor had been in a committed relationship with her partner for forty years prior to their marriage in 2007. Yet she stated that the transformation after entering into the legal union “was profound” and that she has “asked everybody since who gets married after long-term relationships, ‘Did it feel different the next day?’ and the answer is always ‘Yes, absolutely.’”